2004
DOI: 10.4049/jimmunol.172.1.475
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells from Malaria-Infected Mice Are Fully Functional APC

Abstract: Malaria infection has long been associated with diminished T cell responses in vitro and more recently in experimental studies in vivo. Suppression of T cell-proliferative responses during malaria has been attributed to macrophages in a variety of murine and human systems. More recently, however, attention has been directed at the role of dendritic cells in this phenomenon, with several studies suggesting that maturation of dendritic cells is inhibited in vitro by the presence of malaria-infected E. In the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
85
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 34 publications
9
85
3
Order By: Relevance
“…1G). This probably explains why others have not found this CD11c + cell-mediated inhibitory effect on T cells in mice during early infection [41]. We also found a CD8 + T cell inhibitory activity in the incubation media of CD11c -cells at day 5 of infection, that may be related to the one described for CD4 + T cells [42].…”
Section: When Equal Numbers Of Cd8supporting
confidence: 58%
“…1G). This probably explains why others have not found this CD11c + cell-mediated inhibitory effect on T cells in mice during early infection [41]. We also found a CD8 + T cell inhibitory activity in the incubation media of CD11c -cells at day 5 of infection, that may be related to the one described for CD4 + T cells [42].…”
Section: When Equal Numbers Of Cd8supporting
confidence: 58%
“…Studies have found that dendritic cell (DC) 3 function is compromised during Plasmodium falciparum infections and suggested that this was a factor in the pathogenesis of severe disease (1,2). Similarly, studies of rodent P. berghei infections have also found that DC functions are compromised following infection (3)(4)(5) but other studies have found that DCs from mice infected with P. chabaudi or P. yoelii were fully functional (6,7).…”
mentioning
confidence: 98%
“…We therefore hypothesized that the DCs isolated from mice during acute infection would stimulate high levels of IFN-␥ by responding T cells, but DCs isolated later would preferentially stimulate activation of anti-inflammatory T cells. In previous studies, we established the first part of this hypothesis by showing that DCs isolated from day 6 after infection with P. yoelii stimulate high levels of IFN-␥ by naive T cells in an IL-12-dependent manner (11). In this study, we have investigated the function of DCs isolated from later stages of infection.…”
mentioning
confidence: 99%